An improved method for the separation of carotenoids and carotenoid isomers by liquid chromatography–mass spectrometry. Issue 2 (13th December 2020) - Li, Shuang; Tang, Xinyi; Lu, Yingying; Xu, Jilin; Chen, Juanjuan; Chen, Haimin
Abstract: Carotenoids consist of a series of conjugated isoprene units that are characteristically highly conjugated through double bonds, leading to the formation of many isomers that are susceptible to oxidation and other chemical modifications. Extreme hydrophobicity and high complexity make carotenoids difficult to identify and quantify. We implemented the use of a common Syncronis C18 column with strong eluting solvent, here isopropanol, to successfully separate a mixture of 23 carotenoids standards with different structural properties. In addition, the method differentiated between three groups of isomeric carotenoids (lycopene/δ‐carotene/γ‐carotene/ε‐carotene/α‐carotene/β‐carotene, α‐cryptoxanthin/β‐cryptoxanthin, and zeaxanthin/lutein) by optimizing the gradient profile and using liquid chrmatography–mass spectrometry. The LOD ranged from 0.05 to 5.51 ng/mL, and the recovery of carotenoids in Mytilus coruscus was from 63.54 to 93.25%, with standard deviations <10%. Twenty‐five carotenoids were detected with a total content of 857 ± 55.1 mg/kg, and three isomeric carotenoids were identified: ε‐carotene, α‐carotene, and β‐carotene. Our results show that this methodology is a significant improvement over other alternatives for analyzing carotenoids because of its compatibility with carotenoids of different categories, and most importantly, its ability to resolve isomeric carotenes, which is significant not only for assessing carotenoid species, but also for the tracing of metabolic pathways of carotenoids.